Similar or Different Neuropsychological Profiles? Only Set Shifting Differentiates Women With Bipolar vs. Borderline Personality Disorder - Michopoulos, Ioannis; Tournikioti, Kalliopi; Paraschakis, Antonios; Karavia, Anna; Gournellis, Rossetos; Smyrnis, Nikolaos; Ferentinos, Panagiotis (Frontiers in Psychiatry, 2021)
There is ongoing debate about the similarities and differences between bipolar disorder (BD) and borderline personality disorder (BPD). Very few studies have concurrently assessed their neuropsychological profile and only on a narrow array of neuropsychological tests. We aimed to investigate the differences of these two patient groups on visual memory, executive function and response inhibition. Twenty-nine BD patients, 27 BPD patients and 22 controls (all female) were directly compared on paired associates learning (PAL), set shifting (ID/ED), problem solving (SOC) and response inhibition (SSRT) using Cambridge Neuropsychological Test Automated Battery (CANTAB). Rank-normalized outcomes were contrasted in one-way ANOVA tests. Discriminant analysis was finally performed to predict BD or BPD patient status. BD patients performed significantly worse than controls on all tasks. BPD patients performed significantly worse than HC on all tests except SST. Significant differences between the two patient groups were recorded only on ID/ED, where BPD patients performed worse (p=0.04). A forward stepwise discriminant analysis model based on ID/ED, age and SOC predicted correctly patients’ group at 71.7% of cases. This study is the first to show that BPD patients display more deficits than BD patients when directly compared on the set shifting executive function test, a marker of impaired fronto-limbic connectivity. Discerning BD from BPD patients through neuropsychological performance is promising but would improve by using additional subtler tests and psychometric evaluation.